A requirement of TolC1 for effective survival, colonization and pathogenicity of Actinobacillus pleuropneumoniae. (September 2019) - Li, Ying; Cao, Sanjie; Zhang, Luhua; Yuan, Jianlin; Zhao, Qin; Wen, Yiping; Wu, Rui; Huang, Xiaobo; Yan, Qigui; Huang, Yong; Ma, Xiaoping; Han, Xinfeng; et al.
Abstract: To establish infection in the host, pathogens have evolved sophisticated systems to cope with environmental conditions and to protect cells against host immunity. TolC is the outer membrane channel component of type 1 secretion systems and multidrug efflux pumps that plays critical roles during the infection process in many pathogens. However, little is known about the exact roles of TolC1 in the pathogenicity of A. pleuropneumoniae, an etiological agent of the porcine contagious pleuropneumoniae that causes severe respiratory disease. In this study, deletion of tolC1 causes apparent ultrastructural defects in A. pleuropneumoniae cell examined by transmission electron microscopy. The tolC1 mutant is hypersensitivity to oxidative, osmotic and acid challenges by in vitro stress assays. Analysis on secreted proteins shows that the excretion of ApxIIA and an ApxIVA-like protein, ApxIVA-S, is abolished in the absence of TolC1. This result confirms the essential role of TolC1 in the secretion of Apx toxins and this is the first identification of an ApxIVA-like protein in in vitro culture of A. pleuropneumoniae. Besides, disruption of TolC1 leads to a significant attenuation of virulence in mice by an intraperitoneal route of A. pleuropneumoniae. The basis for the attenuation is further investigated using a mouse intranasal infection model, which reveals an impaired ability to colonize and induce lesions in the lungs for the loss of TolC1 of A. pleuropneumoniae. In conclusion, our findings demonstrate significant roles of TolC1 in facilitating bacterial survival in hostile conditions, maximum colonization as well as pathogenicity during the infection of A. pleuropneumoniae . Highlights: Deletion of TolC1 causes apparent ultrastructural defects in A. pleuropneumoniae cell. The tolC1 mutant is hypersensitivity to oxidative, osmotic and acid challenges. ApxIIA and ApxIVA-like toxins are both secreted in a TolC1-dependent manner. The first identification of an ApxIVA-like protein in in vitro culture of A. pleuropneumoniae. Deletion of TolC1 leads to a significant attenuation of virulence in mice .